2020
DOI: 10.25796/bdd.v3i4.57953
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new rapid-diagnostic test for peritonitis in peritoneal dialysis: the PERIPLEX® device.

Abstract: In 2017, the British company MOLOGIC developed a new rapid-diagnostic test (PERIPLEX®) for the diagnosis of peritonitis in patients undergoing peritoneal dialysis. This single-use test is based on the detection in dialysate of two biomarkers of bacterial infection: Interleukin-6 (IL-6) and matrix metalloproteinase-8 (MMP-8). The test was evaluated in a prospective multicenter study including 10 centers from the RDPLF (French Language Peritoneal Dialysis Registry). A total of 184 tests were performed; 86 tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Our study showed higher diagnostic accuracy for the MMP-8 and IL-6-based POCT compared to previously evaluated urinary strips [34,44]. The PERiPLEX ® system utilizes a lateral flow assay to MMP-8 and IL-6, utilizing peritoneal dialysate derived from a dialysis effluent as significant inflammatory indicators with high concentrations during sepsis cases [29,45].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our study showed higher diagnostic accuracy for the MMP-8 and IL-6-based POCT compared to previously evaluated urinary strips [34,44]. The PERiPLEX ® system utilizes a lateral flow assay to MMP-8 and IL-6, utilizing peritoneal dialysate derived from a dialysis effluent as significant inflammatory indicators with high concentrations during sepsis cases [29,45].…”
Section: Discussionmentioning
confidence: 68%
“…Consequently, MMP-8 and IL-6-based POCT might be superior to urinary strips in detecting PDRP, rapidly diagnosing or excluding PDRP, and preventing delays in initiating antibiotic therapy [ 17 ]. An evaluation of PERiPLEX ® yielded identical values for sensitivity and a negative predictive value but lower specificity and positive predictive value (88%) [ 44 ]. Taken together, our analysis, viewed in conjunction with previous investigations, suggests that the PERiPLEX ® POCT might be beneficial in the early detection of PDRP.…”
Section: Discussionmentioning
confidence: 99%
“…New POC technology has been used for the diagnosis of peritonitis in peritoneal dialysis (PD) patients 7 .…”
Section: Analysis Of Peritoneal Dialysis Fluid and Salivamentioning
confidence: 99%
“…New POC technology has been used for the diagnosis of peritonitis in peritoneal dialysis patients (7). Although not yet trialed at home, if successful, it could aid in the triage of which patients require hospital attendance, and it could avoid unnecessary travel and anxiety for those who do not.…”
Section: What Is Currently In Development?mentioning
confidence: 99%
“…Within nephrology, point-of-care testing (POCT) at home has recently received significant interest for a variety of applications [ 3 , 4 , 5 , 6 ]. However, none of these approaches currently exist in wearable form.…”
Section: Introductionmentioning
confidence: 99%